Ionospheric anomalies immediately before Mw7.0–8.0 earthquakes. Issue 8 (2nd August 2017) - He, Liming; Heki, Kosuke
Abstract: Recent observations suggested that ionospheric anomalies appear immediately before large earthquakes with moment magnitudes ( M w ) of 8.2 or more. Do similar phenomena precede smaller earthquakes? Here we answer this question by analyzing vertical total electron contents (VTEC) observed near the epicenters before and after 32 earthquakes with M w 7.0–8.0 using data from nearby Global Navigation Satellite Systems stations. To detect anomalies, we defined the reference curves to fit the observed VTEC and considered the departure from the curves as anomalies. In estimating the reference curves, we excluded time windows, prescribed for individual earthquakes considering M w, possibly affected by earthquakes. We validated the method using synthetic VTEC data assuming both preseismic, coseismic, and postseismic anomalies. Out of the 32 M w 7.0–8.0 earthquakes, eight earthquakes showed possible preseismic anomalies starting 10–20 min before earthquakes. For earthquakes of this M w range, we can observe preseismic ionospheric changes probably when the background VTEC is large, say 50 TECU (total electron content unit, 1 TECU = 10 16 el m −2 ) or more. Key Points: Ionospheric TEC changes immediately before 8 out of 32 M w 7.0–8.0 earthquakes Validation of the reference curve method by numerical tests Preseismic ionospheric anomalies emerge when background VTEC is large